Communication systems : analog and digital - Sharma, Sanjay (S.K. Kataria, 2012)
Communication systems : analog and digital / Sharma, Sanjay. -- New Delhi: S.K. Kataria, 2012 621.382 Sh532e5 5th rev. ed. No. of Copies : 1